ANALISIS DAYA SAING EKSPOR UDANG BRATASENA ADIWARNA PASCA PEMUTUSAN HUBUNGAN KERJA PETAMBAK DAN PERUSAHAAN - Rachmawati, Tety; Lestari, Rahayu; Nabila, Nuzul Inas (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2021)
The termination of the employment relationship between the farmers and the company has changed the shrimp farming pattern in Bratasena Adiwarna. Prior to termination of employment, Bratasena was the largest shrimp exporter in Indonesia. This study aims to analyze the competitiveness of Bratasena shrimp exports, after the termination of employment between farmers and companies. In addition, this research also aims to see the contribution of Bratasena shrimp exports in an effort to support the increase in shrimp exports in Lampung Province following the target of Lampung as the National Shrimp Granary. Data obtained by reviewing several primary and secondary documents and in-depth interviews with several sources, namely farmers, the head of the export division of PT. Central Pertiwi Bahari, as well as the Head of the Office of Marine Affairs and Fisheries in Lampung Province. This study uses a quantitative approach with the calculation of RCA (Revealed Comparative Advantage) to find the value of Bratasena shrimp export competitiveness and market share analysis to see the contribution of Bratasena shrimp exports to the increase in fisheries exports in Lampung Province. The results of this study indicate that the export competitiveness value is quite strong for Bratasena shrimp exports and the contribution of Bratasena shrimp exports to fisheries exports in Lampung Province is also quite large. However, after termination of employment between farmers and companies, the value of export competitiveness and contribution of Bratasena shrimp has decreased. Keywords: competitiveness, export, shrimp